2020
DOI: 10.1017/cts.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy health in POWERMOM participants living in rural versus urban zip codes

Abstract: Background: Pregnant women living in rural locations in the USA have higher rates of maternal and infant mortality compared to their urban counterparts. One factor contributing to this disparity may be lack of representation of rural women in traditional clinical research studies of pregnancy. Barriers to participation often include transportation to research facilities, which are typically located in urban centers, childcare, and inability to participate during nonwork hours. Methods: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While previous studies have shown the importance of remote monitoring of individuals, extending health research beyond the limits of brick and mortar health systems 33 , 34 , additional disparities are introduced when the study relies on wearable sensors, due to reduced accuracy for certain skin tones 35 and unequal access to this digital technology 36 . The decreasing cost of wearable sensors (some now less than $35) and the inner adaptability of our detection algorithm to any sensor and any given level of engagement of the participant with the in-app system will hopefully help in decreasing the barriers for underserved and underrepresented populations.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have shown the importance of remote monitoring of individuals, extending health research beyond the limits of brick and mortar health systems 33 , 34 , additional disparities are introduced when the study relies on wearable sensors, due to reduced accuracy for certain skin tones 35 and unequal access to this digital technology 36 . The decreasing cost of wearable sensors (some now less than $35) and the inner adaptability of our detection algorithm to any sensor and any given level of engagement of the participant with the in-app system will hopefully help in decreasing the barriers for underserved and underrepresented populations.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have shown the importance of remote monitoring of individuals, extending health research beyond the limits of brick and mortar health systems, 32,33 additional disparities are introduced when the study relies on wearable sensors, due to reduced accuracy for certain skin tones 34 and unequal access to this digital technology. 35 The decreasing cost of wearable sensors (some now less than $35) and the inner adaptability of our detection algorithm to any sensor and any given level of engagement of the participant with the in-app system will hopefully help in decreasing the barriers for underserved and underrepresented populations.…”
Section: Discussionmentioning
confidence: 99%
“…This selection bias results in homogenous study cohorts that do not fully represent the diversity of the real-word patient population, thus creating evidence that only applies to a limited group of patients and further propagates health disparities [69]. The decentralized study approach can leverage directto-participant engagement using digital recruitment methods through social media networks, apps, and other online channels without geographic restrictions [70,71]. Sleep research may be able to move towards the same idea on a large scale with the utilization of wearables for fully remote sleep tracking [72].…”
Section: Where We Might Be Headed: Decentralized Digital Studiesmentioning
confidence: 99%